The Possible University-Industry Partnership between DRB-HICOM and University Malaysia Pahang - Arulselvi, Uthayakumaran; Normah, Othman (Scientific & Academic Publishing, 2012)

(untitled)
University- industry relationships are highly heated topics which rope in the high economic value, political and the constant academic interest among industry scientists and the academicians. In the shift of the present economic world, the university industry partnership has co-lateral relationship in which one cannot fulfil the existing job market without another. The knowledge and technological transfer is a catalyst the industry's innovation. It not only narrows the paradigm of knowledge to one per se but it has wider access that might be fruitful to the industry and also the partnering university. The purpose of this paper is to investigate the possible university-industry relation between DRB-HICOM and University Malaysia Pahang and the factors that might affect the knowledge flow between the partnerships. The data for this paper was collected through an interview with an officer from DRB-HICOM. DRB-HICOM has sound expectations of the company employees. They welcome the partnership and also gave suggestions to improve the engineering curriculum of the university for a brighter and greater good for UMP students.